2001
DOI: 10.1089/10507250152039118
|View full text |Cite
|
Sign up to set email alerts
|

The ThyroMobil Model for Standardized Evaluation of Iodine Deficiency Disorder Control in Indonesia

Abstract: Indonesia used to be affected by varying degrees of iodine deficiency. Salt iodization has been the adopted strategy on a national basis since 1979. The prevalence of goiter in school-age children (SAC) determined by palpation subsequently markedly decreased within the next 15 years. The objective of the present work was to perform an updated evaluation of the status of iodine nutrition in Indonesia by using standardized methods for the measurement of thyroid volume by ultrasounds and the concentration of urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…We used a purpose‐built vehicle known as a “ThyroMobil” (Merck, Darmstadt, Germany), which has been used for similar studies of iodine nutrition in other countries 12 . ‐ 14 At each school, students who brought their first morning urine sample to school with a pre‐labelled specific identification number were registered, weighed and their height was measured (to calculate body surface area [BSA]) and they underwent a thyroid ultrasound scan.…”
Section: Methodsmentioning
confidence: 99%
“…We used a purpose‐built vehicle known as a “ThyroMobil” (Merck, Darmstadt, Germany), which has been used for similar studies of iodine nutrition in other countries 12 . ‐ 14 At each school, students who brought their first morning urine sample to school with a pre‐labelled specific identification number were registered, weighed and their height was measured (to calculate body surface area [BSA]) and they underwent a thyroid ultrasound scan.…”
Section: Methodsmentioning
confidence: 99%
“…Since their introduction in 1997, the recommended normative values for thyroid volume in children have been revised on two occasions. The validity of the 1997 WHO/ICCIDD recommended values was challenged by a number of studies, including surveys using a ThyroMobil [22]. A new set of international reference values for thyroid volume assessed by ultrasound examination, based on studies of children living in areas of long-term iodine sufficiency, was released in 2003 [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO/UNICEF/ICCIDD criteria [21, 22], the proportion of the population with UIC less than 100 µg/l should not exceed 50% and those with UIC less than 50 µg/l should not exceed 20%. Our UIC corresponds exactly to those reported earlier in Egypt and from iodine-sufficient areas such as Campania in southern Italy (median UI = 80 µg/l) [31], Switzerland (median UI = 150 µg/l) [32], Malaysia (median UI = 132.8 µg/l) [6], the Netherlands (median UI = 154.4 µg/l) [26], and Australia (median UI = 132.8 µg/l) [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Djokomoeljanto et al, the protein intake can reduce the occurrence of IDD and improve the condition of the disease in endemic IDD. 25 According to Mayes, the adequacy of protein in endemic goiter area is very beneficial to its role in reducing the prevalence of goiter, if protein intake is insufficient, the thyroid hormone is unable to form tiroglobulin. 26 The analysis of this study concluded that especially in young children in the endemic goiter should be anticipated adequacy of the protein.…”
mentioning
confidence: 99%